Manoel Bomfim e a crítica republicana democrática : uma nova tradição interpretativa do Brasil - Marina Naves Batista (2022)
Manoel Bomfim presented na analytical and normative Field that translated the most advanced democratic political thought, from the period from the end of the monarchy to the 1930 revolution. He formulated na innovative, systematic and coherent historical interpretation of Brazil and political and social dynamics. No thinker of this period linked the defense of popular sovereignty to the critique of the oligarchic policies of the Brazilian State. He was able to identify persistent conservatism in the dynamics of political classes, by shifting the problem of racial theories used to explain the country's inequalities, which found fertile ground for reception in Brazil. Revisiting the work of Manoel Bomfim with the support of the theoretical framework of republicanism makes it possible to centrally highlight a conceptual core of the republican lexicon in his thought. From the analysis of the critical fortune of hiswork, it is identified that because it is Unknown to its most recognized interpreters, the use of the republican lexicon in the author's narrative went unnoticed. The effortt to identify Manoel Bomfim as a thinker of the republican tradition makes it possible to explicitly delimit him from other traditions that existed in the First Republic, for example, in relation to oligarchic liberalism and positivism. Analyzes that emphasize the importance of the republican lexicon in the formation process of modern political thought have gained space in the history of political thought since the 1960s. Authors such as Hans Baron, Skinner, Pocock, and, in Brazil, Newton Bignotto, Heloisa Starling, to we stick with just a few, they favored breaking na old historiographical paradigm – which saw Marxism as the first language competing with the liberal tradition – to bebroken. Thus, in the wake of this movement that, in different parts of the Western world, has given greater complexity to the studies of political thought, the work proposes to highlight how the work of Manoel Bomfim is fundamentally based on central elements of the republicanism tradition. In relation to Brazilian Political Thought, this work would fit into the attempts to interpret Brazilian political thought from thepolitical traditions that formed the West, such as some approaches by Wanderely Guilherme dos Santos and Christian Lynch. It starts from the Idea that it is possible to speak in matrices of republicanism, because there is a political language shared over time, but which responds to contingent problems for the analysis of Brazilian Political Thought. It starts with the dialectical movement of the contextual or historical relationship as constitutive dimensions of the method of investigation of the history of ideas.